PERJUANGAN DANUDIRJA SETIABUDI DALAM BIDANG PENDIDIKAN DI HINDAI-BELANDA 1912-1914 DAN RELEVANSINYA DENGAN PEMBELAJARAN SEJARAH KELAS XI SMA - Wulandari, Sri (Candi, 2015)
The purpose of this study were to describe: (1) a history of Danudirja Setiabudi, (2) the politics and education alstruggle of Danudirj aSetiabudi in the Dutch East Indies, (3) the effect of Setiabudi Danudirja struggle against the colonial government and Indieseducational policy, (4) the relevance of Danudirja Setiabudi seducational thought in 1912-1942 at Dutch East Indies towards material of historical learning at class XI Senior High School.In accordance with that objectives, this research used the historical method. This research took place in Monument Press, Rekso Pustaka Library Surakarta. Data were collected through literature study and analysis of primary sources such as books by Danudirja Setiabudi, newspapers and etc. Data analysis techniques in this research using historical analysis that is technical analysis emphasis on sharpness in the interpretation of historical data.Based on the results can be concluded: (1) Danudirja Setibudi born of the couple Auguste Henri Edouard Douwes Dekker, a Dutchman and his mother Louisa Margaretha Neumann.  This shows Danudirja Setiabudi are descendants of Indonesian or mixture included in group Indies. Danudirja Setiabudi as anIndis get a better education than the indigenous people. (2) Danudirja Setiabudi see gaps arise in him the desire transform and express his desire. The path chosen is journalism. Through newspapers Danudirja Setiabudi try express an opinion on the colonial government. Besides journalism Danudirja Setiabudi establish political parties with Ki Hajar Dewantoro and Tcipto Mangun Kusumo named Indische Partij. After this political field failed Danudirja Setiabudi continue his struggle in education by establishing Ksatrian Instituut School in Bandung. (3) As a result of the Setiabudi Danudirja struggle weremake the colonial government get a new provision that all organizations deemed not cooperative with the Dutch government then did not get the recognition of legal entities from the colonial government. His struggle in education give new color for education in the Dutch East Indies, where the school is formed Danudirja Setiabudi embed understand love of country which raised the understanding of nationalism in Ksatrian Instituut students. (4) Setiabudi Danudirja thinking in the field of education is still relevant to this day. Nasioanlisme is understood love of the homeland and a willing to sacrifice for the nation of Indonesia. It is closely related to classroom learning materials at class XI of Senior High School about the national movement.